2012
DOI: 10.4067/s0370-41062012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Efecto metabólico de la metformina en adolescentes obesas con riesgo de diabetes mellitus tipo 2

Abstract: Metabolic effect of metformin in obese adolescents at risk of diabetes mellitus type 2In adults, metformin promotes weight loss and prevents the development of type 2 diabetes mellitus (DM2). However, these effects have not been demonstrated in adolescents at risk for DM2. Objective: To analyze the anthropometric and metabolic impact of metformin in obese adolescents at risk for DM2. Patients and Methods: A double-blind, placebo-controlled study was conducted in 19 obese female adolescents at risk for DM2. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Proportion female ranged from 28% 36 to 100%. 57 Most participants were White; the proportions of other race and ethnicity ranged from 0% 37 to 63%. 64 Mean BMI ranged from 26.2 58 to 41.7 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Proportion female ranged from 28% 36 to 100%. 57 Most participants were White; the proportions of other race and ethnicity ranged from 0% 37 to 63%. 64 Mean BMI ranged from 26.2 58 to 41.7 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The update searches identified 1287 records, of which 14 new RCTs 30–43 (41 records) were included and combined with 21 RCTs 44–64 (33 records) from the Cochrane review, 12 making a total of 35 RCTs. Of the 35 included trials, two were identified from trial registry searches alone and are terminated trials (NCT02273804 and NCT03338296) 30,31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations